Structural insights into Escherichia coli phosphopantothenoylcysteine synthetase by native ion mobility–mass spectrometry. Issue 21 (5th November 2019) - Chan, Daniel Shiu-Hin; Hess, Jeannine; Shaw, Elen; Spry, Christina; Starley, Robert; Dagostin, Claudio; Dias, Marcio V. B.; Kale, Ramesh; Mendes, Vitor; Blundell, Tom L.; Coyne, Anthony G.; Abell, Chris
Abstract: CoaBC, part of the vital coenzyme A biosynthetic pathway in bacteria, has recently been validated as a promising antimicrobial target. In this work, we employed native ion mobility–mass spectrometry to gain structural insights into the phosphopantothenoylcysteine synthetase domain of E. coli CoaBC. Moreover, native mass spectrometry was validated as a screening tool to identify novel inhibitors of this enzyme, highlighting the utility and versatility of this technique both for structural biology and for drug discovery.